Model Tata Bangunan dan Lingkungan Binaan yang Bermitigasi Bencana di Pulau Kodingareng Lompo - Andi Muhammad Ikhsan; Gusti Hardyanti Musda (Universitas Indraprasta PGRI, 2023)
Coastal regions, mainly small islands, are very at risk of being affected so long as sea level upward thrust will result in full-size losses. so as to avoid those losses, it is necessary to manage small islands the use of a neat version of buildings and the surroundings the usage of a dynamic/temporal spatial method. Kodingareng Island means one island within the metropolis of Makassar, precisely in the Sangkarang Islands District, with a place of 0.48 km2. The small and constrained area of the island will virtually be ruled by the increase of residential buildings consistent with population increase. This observe pursuits to determine the level of vulnerability of the place and to use techniques in spatial making plans based totally on catastrophe mitigation on Kodingareng Lompo Island. The research technique used on this research is a qualitative narrative using discipline commentary and interview strategies. Mitigation is the number one place to begin of disaster control. With mitigation, efforts are made to lessen and/or alleviate the effects/sufferers due to a catastrophe on human souls, belongings, and the environment. so that the formation of the mitigation approach as a way to be achieved is to set an instance of the association expected through the humans based at the typological requirements of Kodingareng Island.